Hospitalizations due to falls among elderly Brazilians and related costs under the Public Health System - Barros, Iarema Fabieli Oliveira de (2015)
The aim of this research was to analyze the hospitalizations for falls among elderly Brazilians and related costs under the Public Health System. Directed study of secondary data published by the Ministry of Health online form by the Department of Health System Information, related to morbidity due to falls involving elderly residents in Brazil from 2005 to 2010. The data analysis was made through descriptive statistics (absolute frequencies and percentages) according to the variables: gender, age, health macro-regions, average time hospital stay and hospital admission authorization value paid (AIH). 399,681 hospital admissions were analyzed by falls in elderly Brazilians, and 59.781% occurred in females. The total value of AIH paid was R $ 464,874,275.91, and that total 59.66% of these expenditures were intended to females. We realize the importance of health professionals as health promoter in order to support falls prevention policies.